Hubungan Antara Iklan Gojek BTX terhadap Minat Konsumen menggunakan Aplikasi Gojek - Siti Elda Nursafitri; Satya Indra Karsa (UNISBA Press, 2022)
Abstract. The development of technology is currently very busy being used by the community, and the presence of advertising can help promotional activities run smoothly, by placing advertisements through electronic media, print media and outdoor media can provide the needs of the audience indirectly with creative ideas that are displayed by offering various kinds goods and services. The purpose of this study was to determine the relationship between the frequency, attention, duration of Gojek BTX advertisements with consumer interest in Gojek application users. The method used is this study, using the Uses & Gratification Theory from Blumer and Katz, using quantitative research methods with a correlational approach. The population selected in this study were students of the Faculty of Communication, Islamic University of Bandung who had watched the Gojek BTX advertisement, totaling 1,111 people, the determination of the sample was random sampling which included probability sampling. After being calculated using the Slovin formula, there were 92 respondents. The data processing technique used descriptive analysis and inferential analysis (Rank Spearman) through SPSS software. The result of the relationship between Gojek BTX advertising and consumer interest using the Gojek application